PERAN KEPALA MADRASAH DALAM PENGEMBANGAN BUDAYA LITERASI AL-QUR'AN PADA SISWA MTSS ULUMUL QUR'AN ACEH TENGAH - Fitra Fitra; Sufriadi Sufriadi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the role of the madrasa principal in developing the Qur’anic literacy culture among students at MTsS Ulumul Qur’an Bebesen, Central Aceh. This research employed a descriptive qualitative approach using observation, interviews, and documentation involving the madrasa principal, vice principal for student affairs, Tajweed teacher, and students. Data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings reveal that the Qur’anic literacy culture is implemented regularly every morning through the recitation of short surahs, religious speeches, Surah Yasin, and collective prayers. The madrasa principal plays a significant role in planning, organizing, supervising, and evaluating the program to ensure its systematic and sustainable implementation. The program positively improves students’ Qur’an reading skills, particularly in fluency, pronunciation (makhraj), and tajwid accuracy, while also fostering religious character, discipline, and responsibility. The novelty of this study lies in identifying a leadership model that integrates managerial functions, supervision, and religious culture development in promoting a sustainable Qur’anic literacy culture within a pesantren-based madrasah.